Method of reduced description in theory of long wave nonequilibrium fluctuations - Peletminskii, S.V.; Slyusarenko, Yu.V. (Вопросы атомной науки и техники, 2001)
The regular method for construction of kinetic equations of long-wave fluctuation theory is developed in a microscopic approach on the base of generalization of the kinetic Bogolyubov theory. The transition to the hydrodynamic theory of long-wave fluctuations is investigated in detail. The derived hydrodynamic equations describe a turbulent liquid state. The concept of nonequilibrium entropy for fluctuating systems is introduced. The H-theorem is proved.